MLL5 suppresses antiviral innate immune response by facilitating STUB1-mediated RIG-I degradation - Peipei Zhou (Nature Portfolio, 2018)
MLL5 is an essential epigenetic modifier involved in cell cycle progression, chromatin architecture and hematopoiesis. Here the authors establish that MLL5 suppresses the innate immune response in a murine model of virus infection by targeting and promoting degradation of RIG-I.